Inorganic benzene valence isomers - Ota, Kei (2022)
It has been computationally proposed that there are more than 200 possible isomeric structures for the C6H6 molecule, among which benzene (CH)6 represents the most thermodynamically stable molecule and its chemistry has been extensively developed. Three benzene valence isomers (CR)6, namely, prismane, Dewar benzene, and benzvalene, have also been synthesized to date. Incorporation of heteroatoms in the skeletal frameworks allows access to inorganic analogues of benzene and its valence isomers, which have attracted considerable attention due to their peculiar structural and electronic features. Experimentally, more than 30 examples of inorganic benzene and its valence isomers have been developed and characterized so far. In this contribution, their synthesis and characterization, as well as their stability and chemical properties, are discussed.